Cardiovascular and haematological events post COVID‐19 vaccination: A systematic review. Issue 3 (29th December 2021) - Al‐Ali, Dana; Elshafeey, Abdallah; Mushannen, Malik; Kawas, Hussam; Shafiq, Ameena; Mhaimeed, Narjis; Mhaimeed, Omar; Mhaimeed, Nada; Zeghlache, Rached; Salameh, Mohammad; Paul, Pradipta; Homssi, Moayad; et al.
Abstract: Since COVID‐19 took a strong hold around the globe causing considerable morbidity and mortality, a lot of effort was dedicated to manufacturing effective vaccines against SARS‐CoV‐2. Many questions have since been raised surrounding the safety of the vaccines, and a lot of media attention to certain side effects. This caused a state of vaccine hesitancy that may prove problematic in the global effort to control the virus. This review was undertaken with the aim of putting together all the reported cardiovascular and haematological events post COVID‐19 vaccination in published literature and to suggest possible mechanisms to explain these rare phenomena.